Relationship between strategic orientation and organizational performance an exploratory study of Philippine companies - Racelis, Aliza D. (Philippine Management Review, 2006)
Questions have always been posed about organizational performance and its many determinants. The study and explanation of business competitiveness is a recurring theme examined by academics, consultants and practitioneres (Aragon-Sanchez and Sanchez-Marin, 2005). While firm performance is a multi-aspect phenomenon that is found to be influenced by a multiplicity of factors, such as culture, leadership, human resource management practices, the environment, market orientation, and overall company strategy, the growing literature on 'strategic thinking' or 'strategic management' points to competitive strategic management as one of the more influential determinants of firm success. This study is an attempt to corroborate claims that strategic orientation is related to higher organizational performance. Using the Ozen and Ulengin (2001) framework for the identification of strategic "thoughts", a content analysis of annual reports of Philippine firms is performed to gather data relating to both those strategic variables and organizational performance variables. The financial performance variables that turned out having any significant relationship with the strategy variables are Profit Margin and Debt Ratio. Likewise, the only strategy variables that turned out having any significant relationship with the organizational performance variables are: 1) consistent brand and image strategies, 2) producing products that have competitive advantages, and 3) developing core business areas through investment. While the sample size needs to be enlarged, the implication of these findings for practitioners is that strategic orientations shown to have a significant relationship with financial performance should lead managers to consider adopting those specific strategic orientations in their regular planning routine.